Stability of Runge-Kutta Methods for Neutral Delay Differential Equations - Liping Wen; Xiong Liu; Yuexin Yu (Discrete Dynamics in Nature and Society)
This paper is concerned with the numerical stability of a class of nonlinear neutral delay differential equations. The numerical stability results are obtained for (k,l)-algebraically stable Runge-Kutta methods when they are applied to this type of problem. Numerical examples are given to confirm our theoretical results.